2022
DOI: 10.1016/j.heliyon.2022.e08816
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical effectiveness of steam inhalation against SARS-CoV-2 infection: updates on clinical trials, mechanism of actions, and traditional approaches

Abstract: Steam inhalation therapy can be a contemporary approach for COVID-19 affected patients of all age groups to manage respiratory conditions, though it presently lacks the scientific backing to establish itself as a befitting practice. The age of COVID-19 has facilitated this traditional home remedy to resurface among the general mass as a helpful approach for the prevention and adjuvant treatment of the disease. In this review, the means of SARS-CoV-2 infection and impact of the parameters, namely steam inhalati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Similar findings were reported by other studies in Italy, 32 United States 33 and Ghana. 34 Although, no study has reported dietary modification and supplementation, 35 or established the effectiveness of steam inhalation 36 could prevent COVID-19, Hibino and Hayashida intimated that in the wake of vaccine hesitancy, effective non-pharmaceutical interventions, healthy lifestyles and improved dietary patterns could improve the health of individuals and reduce the risk for COVID-19. 37 Several other studies emphasized the relevance of micronutrients such as zinc and Vitamins in the optimization of immune system and regulating immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by other studies in Italy, 32 United States 33 and Ghana. 34 Although, no study has reported dietary modification and supplementation, 35 or established the effectiveness of steam inhalation 36 could prevent COVID-19, Hibino and Hayashida intimated that in the wake of vaccine hesitancy, effective non-pharmaceutical interventions, healthy lifestyles and improved dietary patterns could improve the health of individuals and reduce the risk for COVID-19. 37 Several other studies emphasized the relevance of micronutrients such as zinc and Vitamins in the optimization of immune system and regulating immune response.…”
Section: Discussionmentioning
confidence: 99%
“…People predicted the therapeutic benefits of medicinal plants before the creation of contemporary therapies [ 2 ]. The use of traditional and unconventional methods to treat various illness conditions is widespread worldwide [ 3 ]. Even in the modern period, plants are still a possible source of therapeutics for serious illnesses like cancer, oxidative stress, diarrhea, depression, fever, and thrombosis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of steam inhalation (local hyperthermia) in the treatment and prevention of Covid-19 is gaining popularity. Its effectiveness was demonstrated in a clinical trial [28]. In one study, [29] were administered five cycles of four minutes for twenty minutes for four consecutive days at a temperature of 55°C and 65°C in the first 4 to 5 min after the initiation of water boiling.…”
Section: Introductionmentioning
confidence: 99%